Uterine stem cells: from basic research to advanced cell therapies. (15th September 2018) - Santamaria, Xavier; Mas, Aymara; Cervelló, Irene; Taylor, Hugh; Simon, Carlos
Abstract: BACKGROUND: Stem cell research in the endometrium and myometrium from animal models and humans has led to the identification of endometrial/myometrial stem cells and their niches. This basic knowledge is beginning to be translated to clinical use for incurable uterine pathologies. Additionally, the implication of bone marrow-derived stem cells (BMDSCs) in uterine physiology has opened the field for the exploration of an exogenous and autologous source of stem cells. OBJECTIVE AND RATIONALE: In this review, we outline the progress of endometrial and myometrial stem/progenitor cells in both human and mouse models from their characterization to their clinical application, indicating roles in Asherman syndrome, atrophic endometrium and tissue engineering, among others. SEARCH METHODS: A comprehensive search of PubMed and Google Scholar up to December 2017 was conducted to identify peer-reviewed literature related to the contribution of bone marrow, endometrial and myometrial stem cells to potential physiological regeneration as well as their implications in pathologies of the human uterus. OUTCOMES: The discovery and main characteristics of stem cells in the murine and human endometrium and myometrium are presented together with the relevance of their niches and cross-regulation. The current state of advanced stem cell therapy using BMDSCs in the treatment of Asherman syndrome and atrophic endometrium is analyzed. In the myometrium, the understanding of genetic and epigenetic defects that result in the development of tumor-initiating cells in the myometrial stem niche and thus contribute to the growth of uterine leiomyoma is also presented. Finally, recent advances in tissue engineering based on the creation of novel three-dimensional scaffolds or decellularisation open up new perspectives for the field of uterine transplantation. WIDER IMPLICATIONS: More than a decade after their discovery, the knowledge of uterine stem cells and their niches is crystalising into novel therapeutic approaches aiming to treat with cells those conditions that cannot be cured with drugs, particularly the currently incurable uterine pathologies. Additional work and improvements are needed, but the basis has been formed for this therapeutic application of uterine cells.